2022
DOI: 10.1186/s12889-022-14169-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of unsuppressed viral load among adults on follow up of antiretroviral therapy at selected public and private health facilities of Adama town: unmached case-control study

Abstract: Background Despite the scale up of antiretroviral therapy (ART), unsuppressed viral load among population taking ART in private and public health facilities is still a public health concern increasing the risk of treatment failure. Studies comprehensively assessing significant predictors of non-suppressed viral load among patients on follow up of AR in public and private health facilities are limited. The objective of the study was to identify predictors of unsuppressed viral load among adult p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…The studies found through database searching and included for the current review were performed between 2016 and 2022 and published between 2018 and 2023. Regarding the study area/region, 7 articles were conducted in the Amhara region [ 20 , 25–30 ], 6 studies in the Oromia region [ 21 , 31–35 ], 5 articles in the South Nation and Nationalities and Peoples of Ethiopia (SNNPE) region [ 19 , 36–39 ], 1 study in the Tigray region [ 40 ], and 2 studies in the Addis Abeba city administration [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies found through database searching and included for the current review were performed between 2016 and 2022 and published between 2018 and 2023. Regarding the study area/region, 7 articles were conducted in the Amhara region [ 20 , 25–30 ], 6 studies in the Oromia region [ 21 , 31–35 ], 5 articles in the South Nation and Nationalities and Peoples of Ethiopia (SNNPE) region [ 19 , 36–39 ], 1 study in the Tigray region [ 40 ], and 2 studies in the Addis Abeba city administration [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ten articles were conducted using a cross-sectional study design [ 19 , 25 , 28 , 32–35 , 37 , 39 , 40 ], 2 studies were conducted using a case–control study design [ 31 , 41 ], 8 studies were conducted using a retrospective cohort study [ 20 , 21 , 26 , 27 , 29 , 30 , 36 , 42 ], and 1 study was conducted using a prospective cohort study [ 38 ]. Nine studies were conducted on first-line ART patients [ 21 , 26 , 31 , 33 , 34 , 36 , 37 , 38 , 42 ], 9 studies were conducted on both first- and second-line ART patients [ 19 , 20 , 25 , 28 , 29 , 32 , 35 , 39 , 40 , 41 ], and 2 were conducted on second-line ART patients [ 27 , 30 ]. The minimum sample size was 152 in the study in Arba Minch [ 38 ], and the maximum sample size was 19 525 in the study in the Tigray region ( Table 1 ) [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found through database searching was performed between 2011 and 2022. Regarding the study area/region, seven studies were conducted in the Amhara region (19,24,25,26,27,28,29), six studies in the Oromia region (20,30,31,32,33,34), ve studies in the South Nation and Nationalities and Peoples of Ethiopia (SNNPE) region (18,35,36,37,38), one study in the Tigray region (39) and two studies in the Addis Abeba city administration (40,41).…”
Section: Characteristics Of the Included Studies In Ethiopiamentioning
confidence: 99%
“…By study design, ten studies were conducted using a cross-sectional study design (18,24,27,31,32,33,34,36,38,39), two studies were conducted using a case control study design (30,40), eight studies were conducted using a retrospective cohort stud (19,20,25,26,28,29,35,41) and one study was conducted using a prospective cohort study (37). Nine studies were conducted on rst-line ART patients (20,25,30,32,33,35,36,37,41), nine studies were conducted on both rst-and second-line ART patients (18, 19,24,27,28,31,34,38,39,40), and two were conducted on second-line ART patients (26, 29). The minimum sample size was 152 taken in the study in Arba Minch (37), and the maximum sample size was 19,525 used in the study in the Tigray region (39) for detail (Table 1).…”
Section: Characteristics Of the Included Studies In Ethiopiamentioning
confidence: 99%